2022
DOI: 10.3389/fcell.2022.822011
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic, Therapeutic, and Prognostic Value of the m6A Writer Complex in Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) has poor prognosis and is usually diagnosed only at an advanced stage. Identification of novel biomarkers is critical to early diagnosis and better prognosis for HCC patients. N6-methyladenosine (m6A) RNA methylation regulators play important roles in the development of many tumors. However, the m6A writer complex, a key executor of m6A methylation modification, has not been independently investigated, and its specific bioinformatics analysis has not yet been performed in HCC. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
(80 reference statements)
0
8
0
Order By: Relevance
“…METTL3, the first identified gene in m6A modification, can interact with Per2 and Arntl to directly mediate the export of mRNA ( Bhattarai et al, 2021 ). METTL14, METTL16, WTAP, VIRMA, ZC3H13, CBLL1, RBM15, and RBM15B are also included in the complex of m6A “writers” ( Meyer and Jaffrey, 2017 ; Wen et al, 2018 ; Gu et al, 2022 ; Shen et al, 2022 ; Su et al, 2022 ). Accordingly, YT521-B homology (YTH) domain family is the main “readers” ( Jones et al, 2022 ) and “erasers” consisting of FTO and ALKBH5 ( Kaur et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…METTL3, the first identified gene in m6A modification, can interact with Per2 and Arntl to directly mediate the export of mRNA ( Bhattarai et al, 2021 ). METTL14, METTL16, WTAP, VIRMA, ZC3H13, CBLL1, RBM15, and RBM15B are also included in the complex of m6A “writers” ( Meyer and Jaffrey, 2017 ; Wen et al, 2018 ; Gu et al, 2022 ; Shen et al, 2022 ; Su et al, 2022 ). Accordingly, YT521-B homology (YTH) domain family is the main “readers” ( Jones et al, 2022 ) and “erasers” consisting of FTO and ALKBH5 ( Kaur et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…First of all, the expression level of METTL14 was identified to be obviously decreased in HCC, which closely correlated with clinicopathological factors, including tumor stage and prognosis (Fig. 3) [125][126][127][128].…”
Section: Liver Cancermentioning
confidence: 90%
“…First of all, the expression level of METTL14 was identified to be obviously decreased in HCC, which closely correlated with clinicopathological factors, including tumor stage and prognosis (Fig. 3 ) [ 125 128 ]. Based on the analysis of data from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO), Liu et al showed the opposite expression level and prognostic value of METTL14 and METTL3 in HCC [ 127 ].…”
Section: Introductionmentioning
confidence: 99%
“…The m6A, m7G, m5C, m1A, m3C, and ψ RNA modifications dynamically regulate the development of HCC, providing new strategies and possibilities for selecting possible therapeutic targets and investigating precisely directed intervention strategies for future HCC therapy (Tian et al, 2019;Bolatkan et al, 2022;Liu et al, 2022;Ren et al, 2022;Tong et al, 2022;Yu et al, 2022). As the most intensively studied RNA modification, m6A, and its regulators regulate the proliferation, migration, invasion, and EMT processes of HCC cells and are promising targets for HCC therapy (Zhou et al, 2019b;Liu et al, 2020a;Wang et al, 2020b;Zhang et al, 2020c;Qu et al, 2020;Wu et al, 2020;Zhu et al, 2020;Li et al, 2021e;Wei, 2021;Gu et al, 2022;Ren et al, 2022). Although m6A in mammalian RNA has been extensively studied, there is currently no evidence for DNA N6 -methyladenine in mammals (Douvlataniotis et al, 2020).…”
Section: Discussionmentioning
confidence: 99%